Effect of earthworms and plants on the efficiency of vertical flow systems treating university wastewater - Lavrnić, Stevo; Cristino, Sandra; Zapater-Pereyra, Maribel; Vymazal, Jan; Cupido, Domenico; Lucchese, Giovanni; Mancini, Benedetta; Mancini, Maurizio L (Environmental science and pollution research international, 2019)
One of the possible ways to improve the operation efficiency of constructed wetlands and to prevent their clogging is the application of earthworms. They have already been successfully applied for vermicomposting and for sludge dewatering and treatment. A few studies have already examined the effect of earthworms on the treatment of wastewater by vertical flow constructed wetlands (VFCWs), but none of them have provided a yearlong research result from an open-air system or compared the effect that different seasons in a temperate climate area can have on these invertebrates. The goal of this research was to estimate the effect that earthworms and plants have on VFCW's operation. Four mesocosms (a filter, a filter with earthworms, a VFCW and a VFCW with earthworms) were built and their influent and effluent water quality was monitored for a period of 1 year. They were fed with wastewater coming from a building of the University of Bologna (Italy). The results have shown that the presence of earthworms in this specific system did not reduce the organic matter content of the substrate, but it has positively influenced plants' growth. However, since neither earthworms nor plants had a statistically significant effect on the effluent quality, it can be concluded that the integration of these invertebrates cannot improve wastewater treatment of vertical flow filters or constructed wetlands.
Keywords: Water Quality; odpad tekutý - odstraňování; Oligochaeta; Waste Disposal, Fluid; odpadní vody; odpadní voda; kvalita vody; Universities; Animals; univerzity; mokřady; Wetlands; Sewage; Italy; Itálie; Wastewater; zvířata